Hanging Ball Game: An Effort to Improve Lower Passing Ability in Volleyball Games - Rustandi, Endi; Suryadin, Tatang; Nurwandi, Agung (Universitas Majalengka, 2024)
This study aims to improve the ability of lower passing in volleyball games through a hanging ball game approach in class IV students of SD Negeri Sukamulya III. This research uses PTK. The subjects of this research are physical education teachers and research partners in this case act as observers or observers during the learning process, while the researchers themselves carry out the learning or as teachers. The object of this research is learning lower passing using the hanging ball game approach. Data collection techniques using observation and tests. The results showed that the lower passing learning activity of class IV students of SD Negeri Sukamulya III. It is evident from 36 students whose activities are not good in pre-cycle activities with an average score of 2.15 in cycle I increased to 2.47 and at the end of cycle II to 3.50 or good qualifications. Learning achievement of lower passing of class IV students of SD Negeri Sukamulya III. There was an increase in the percentage of student learning completeness from 33.33% in pre-cycle activities to 44.44% in cycle I and increased to 80.56% at the end of cycle II. The conclusion of this study shows that through the hanging ball game approach can improve the ability of lower passing in volleyball games in class IV students of SD Negeri Sukamulya III.